Penyuluhan Kesehatan melalui Program GERTAGIMU sebagai Upaya Menangani Masalah Gigi dan Mulut pada Anak - Lalu Muhammad Sadam Husen; Yayan Hardiansah; Lalu Hersika Asmawariza; Vera Yulandasari; Baiq Fiya Apriani; Amalia Mastuti; Reza Indra Wiguna; Baiq Leni Putri Mei Sari; Cindi Ayuwardini; Rian Azhari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Dental and oral health is an integral part of overall health that can affect a person’s quality of life and is an important concern in developing the health of thepopulation of Indonesia and developing countries. According to PDGI in Astannudinsyah, (WHO) World Health Organization states that around the world, 60-90% of school children have cavities, while according to data from PDGI (Indonesian Dentist Association) states that at least 89% of caries sufferers are children. Based on the data above, we are interested in proposing an idea for health education for school-age children, namely how to maintain dental and oral hygiene through the GERTAGIMU (Gerakan Menjaga Kesehatan Gigi dan Mulut) program. GERTAGIMU is one of the health innovation programs as an effort to promote health in the group of school-age children in maintaining dental and oral hygiene. The GERTAGIMU activity aims to increase the knowledge and ability of school-age children in maintaining dental and oral health. The method used is using posters and animated cartoon videos as the target group of school-aged children in grades I and II at SDI Raudatul Husna Kepok Hamlet, the research sample is 64 respondents. The counseling activities carried out in the GERTAGIMU program were in the form of education about dental and oral problems in the school age group of children then the children were taught how to maintain oral and dental hygiene and how to brush their teeth properly and correctly. The result of the GERTAGIMU activity is that it can increase the knowledge of school-age children about how to maintain dental and oral health.